2021
DOI: 10.1038/s41436-021-01134-9
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction of protein subdomain stability in MYBPC3 enables clinical risk stratification in hypertrophic cardiomyopathy and enhances variant interpretation

Abstract: Purpose Variants in MYBPC3 causing loss of function are the most common cause of hypertrophic cardiomyopathy (HCM). However, a substantial number of patients carry missense variants of uncertain significance (VUS) in MYBPC3. We hypothesize that a structural-based algorithm, STRUM, which estimates the effect of missense variants on protein folding, will identify a subgroup of HCM patients with a MYBPC3 VUS associated with increased clinical risk. Methods Am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We anticipate this approach can contribute to reduce the number of DCM patients with unexplained genetic etiology and to inform development of tailored, mechanismbased preventive and therapeutic strategies 3 . Specifically, we envision that emerging high-throughput in silico [46][47][48][49] and in vitro 50 methods will be able to capture pathogenicity potential related to domain destabilization of all possible titin missense variants. Identification of these pathogenic variants is a prerequisite for the development of therapies able to counterbalance domain destabilization, including strategies based on exon skipping 51 or pharmacological chaperones 52 .…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate this approach can contribute to reduce the number of DCM patients with unexplained genetic etiology and to inform development of tailored, mechanismbased preventive and therapeutic strategies 3 . Specifically, we envision that emerging high-throughput in silico [46][47][48][49] and in vitro 50 methods will be able to capture pathogenicity potential related to domain destabilization of all possible titin missense variants. Identification of these pathogenic variants is a prerequisite for the development of therapies able to counterbalance domain destabilization, including strategies based on exon skipping 51 or pharmacological chaperones 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Other tools utilize high-resolution structural data of proteins and the effect that mutations have on protein folding and stability to predict their pathogenicity ( 37 ). A study of people with MYBPC3 VUS using the STRUM tool (evaluating the change in free energy of domain folding upon introduction of a mutation) showed that mutations that produced misfolding were associated with lower event-free survival ( 38 ).…”
Section: Computational and Genomic Methods Used In Identification Of Vusmentioning
confidence: 99%
“…Most HCM-causing mutations within MYBPC3 are missense mutations that are expected to incorporate into the sarcomere, suggesting that these domains have a direct effect on regulatory function ( Flashman et al, 2004 ; Helms et al, 2020 ; Thompson et al, 2021 ). Surprisingly, the central domains C3, C5, and C6 are among the most highly mutated regions in MYBPC3 and are hotspots for pathogenic HCM variants ( Desai et al, 2022 ).…”
Section: Disease-causing Mutations Located In the Central Domains Of ...mentioning
confidence: 99%